Eficiência da seleção visual para produção de massa verde de forragem em Cynodon spp. - Fregulhia, Letícia Mária Costa (2018)
Visual selection is used constantly in the initial stages of selection cycles in breeding programs, aiding in the selection or disposal of genotypes. However, its efficiency in identifying superior genotypes has been questioned in some cultures. Thus, the objective of this work was to verify the efficiency of visual selection for green forage mass production in Cynodon spp. clones. For this purpose, 140 clones of Cynodon spp. together with the Tifton 85 (Cynodon sp.) and Jiggs (Cynodon dactylon) controls, in an enlarged block experiment. The evaluated characters were a note of vigor regarding green mass production and green forage mass production (kg), analyzed using the mixed model approach REML / BLUP. The efficiency of visual selection was estimated by the number of coincidences between plants when different selection strategies were performed. Genetic gains were estimated via genotype values of forage green mass production and vigor score, in the selection intensities where coincidence was obtained between selected plants above 80%. The selection of the BLUP means of the production of green forage mass (BLUP GMP) through selection of the BLUP averages of the vigor note (BLUP VN) resulted in the highest coincidence index (90%) in the selection intensity of 45%. The highest genetic gain was obtained in the intensity of selection of 35%, independent of the strategy. It is concluded that the visual selection in clones of Cynodon spp. for the production of green forage mass is efficient in discarding lower clones in the initial stages of a cycle of selection of the genetic improvement program of the genus Cynodon.